Gastrointestinal toxicity of minor analgesics - Duggan, J. M. (1980)
1 The evidence for the risk of gastric erosions from aspirin is fragmentary. 2 Occult gastric bleeding following aspirin is poorly studied and the skewed distribution is unexplained; platelet factors may be relevant. 3 Overt gastric bleeding may follow aspirin; the risk is probably about one episode per two million doses. 4 There is epidemiological, clinical, experimental and histopathological evidence for an association between chronic aspirin use and chronic gastric ulcer. 5 An alternative to the Davenport hypothesis is proposed to explain the gastric action of aspirin and the non-steroidal anti-inflammatory agents. 6 Paracetamol is probably bland in its gastric actions.